Comparative effectiveness and safety of prasugrel and ticagrelor in patients of acute coronary syndrome undergoing percutaneous transluminal coronary angioplasty: A propensity score-matched analysis - Avik Ray; Ahmad Najmi; Gaurav Khandelwal; Ratinder Jhaj; Balakrishnan Sadasivam (Indian Heart Journal, 2024)
Evidence on comparative effectiveness and safety of prasugrel and ticagrelor post-percutaneous transluminal coronary angioplasty is scarce in Indian population. In a 1:1 propensity score-matched cohort with 71 individuals in each group, the incidence of a composite of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, or coronary revascularization was not significantly different in prasugrel and ticagrelor group (7.04% vs 9.86%; absolute difference, 2.8%; HR, 0.65; 95% CI, 0.21–2.1; p = 0.49). There was no significant difference in bleeding (5.63% vs 9.86%; absolute difference, −4.20%; 95% CI, −13.0%–4.5%) and dyspnea (7.04% vs 12.7%; absolute difference, −5.60%; 95% CI, −15.4%–4.1%).